Patterns of Morphological and Microcirculatory Disorders in the Thyroid Gland Under Microelement Deficiency - Aslonov , O.G. (American Journal of Bioscience and Clinical Integrity, 2026)
The study investigates morphological, morphometric, and microcirculatory changes in the thyroid gland under conditions of microelement deficiency (Mg, Fe, Se, Zn) in white outbred rats. Quantitative analysis revealed a decrease in thyroid gland mass accompanied by pronounced structural remodeling, including thickening of the capsule, reduction in capillary density and diameter, and impairment of microcirculatory function. Morphological alterations were characterized by a decrease in follicular epithelial height, redistribution of follicle size, and increased stromal component, indicating reduced secretory activity and fibrotic processes. The most severe changes were observed under combined microelement deficiency, demonstrating progressive structural and functional deterioration of the thyroid gland. The findings highlight the key role of microelements in maintaining thyroid homeostasis and provide insight into the pathogenesis of endocrine dysfunction under deficiency conditions.